Nilai Intrisik Saham PT Bank Mandiri (Persero) Tbk dengan Metode Relative Valuation - Prihatiningsih, Prihatiningsih (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2018)
This study aims to determine the intrinsic value of PT. Bank Mandiri (Persero), Tbk shares with code shares BMRI, the shares condition, and decisions that can be taken under these conditions. Valuation method used in this study is Relative Valuation. The steps fundamental analysis are macroeconomic analysis, industry analysis and company analysis required to make investment decision on BMRI shares. From the results of study note even the BMRI shares price is overvalued than intrinsic value. Risk seeker investors who haven’t BMRI shares can buy it, and risk seeker investors who have PTPP shares can hold it in their portfolio. Risk averse investors who have the BMRI shares can sell it, and risk averse investors who haven’t BMRI shares can hold to buying.